2019
DOI: 10.48550/arxiv.1905.13736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unlabeled Data Improves Adversarial Robustness

Abstract: We demonstrate, theoretically and empirically, that adversarial robustness can significantly benefit from semisupervised learning. Theoretically, we revisit the simple Gaussian model of Schmidt et al. [35] that shows a sample complexity gap between standard and robust classification. We prove that this gap does not pertain to labels: a simple semisupervised learning procedure (self-training) achieves robust accuracy using the same number of labels required for standard accuracy. Empirically, we augment CIFAR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 23 publications
(79 reference statements)
1
63
0
Order By: Relevance
“…Please see Appendix.B for more details and complete proof. Here the distillation loss is formulated by the prediction accuracy for pseudo-labels generated by a learnt teacher model, which is also considered by [15].…”
Section: Theoretical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Please see Appendix.B for more details and complete proof. Here the distillation loss is formulated by the prediction accuracy for pseudo-labels generated by a learnt teacher model, which is also considered by [15].…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The adversarial training consists of an inner, iterative maximization loop to augment natural examples with adversarial perturbations, and an outer minimization loop similar to normal training. Many different methods have been introduced to improve robustness [77,15,53,92,80,67,95,79,7,82,40,45,57], but all of them are fundamentally based on the principle of training on adversarially augmented examples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, significant efforts have been made to improve the robustness of models without resorting to AT. Proposed solutions cover a wide range of techniques based on curvature regularization [17], robust optimization to improve local stability [23], the use of additional unlabeled data [4], local linearization [21], Parseval networks [5], defensive distillation [19], model ensembles [18], channel-wise activations suppressing [2], feature denoising [29], self-supervised learning for adversarial purification [25], and input manipulations [7,9,15]. All the listed techniques, except those based on input manipulations, require training the model or an auxiliary module from scratch.…”
Section: Related Workmentioning
confidence: 99%
“…for both supervised classifier and attack generator (that ensures misclassification). The recent work [22][23][24] demonstrated that with a properly-designed attacker's objective, AT-type defenses can be generalized to the semi-supervised setting, and showed that the incorporation of additional unlabeled data could further improve adversarial robustness in image classification. Such an extension from supervised to semi-supervised defenses further inspires us to ask whether there exist unsupervised defenses that can eliminate the prerequisite of labeled data but improve model robustness.…”
Section: Introductionmentioning
confidence: 99%